Besieged identity: the National Truth Commission in the revista do Clube Militar (Tempo e Argumento, 2022)
With the creation of the National Truth Commission, in 2011, Brazil has moved forward in the search to overcome the legacy of Civil-Military Dictatorship. However, the traumas experienced during the period are still sources of tension, particularly regarding the memory and the identity of the protagonists of this troubled period of National History. Our proposal is, based on theoretical reference about memory, identity and power, to analyze the military reaction - guided by the memorialist perspective present in texts published by the Military Club Magazine - in defense of the military identity, supposedly threatened by the work of the aforementioned Commission.
Keywords: National Truth Commission; memory; identity; power; Military Club